MEDITASI SEBAGAI WADAH DIALOG ANTAR-UMAT BERAGAMA DAN PENGARUHNYA TERHADAP KEIMANAN PESERTA NON-BUDDHIS (STUDI ATAS MEDITASI UMUM DI VIHARA KARANGDJATI, YOGYAKARTA) - Muhammad Arif; Fuad Hizbillah Fathoni; Muhammad Ya'la 'Ali Sadad (Studia Sosia Religia, 2024)
This study examines public meditation at Vihara Karangdjati, Yogyakarta, as a means of interfaith dialog and its influence on the faith of non-Buddhist participants. Meditation, which is inclusive and open to all, allows interfaith interaction through various dimensions of dialog, such as life dialog, social analysis and ethical reflection, sharing faith experiences, and intra-religious reflection. The results show that meditation at Vihara Karangdjati not only acts as a spiritual practice to achieve inner peace, but also as a bridge that strengthens social solidarity and enriches the spirituality of participants without blurring their religious identity. The influence of meditation on non-Buddhist participants was analyzed using Joachim Wach's theory of religious experience, which includes theoretical, practical, and social dimensions. Non-Buddhist participants felt the benefits of meditation in practicing peace of mind, increasing focus in worship, and creating a space for tolerance and harmony across religions. This research confirms that meditation can be an effective platform for interfaith dialog, strengthening faith, and building harmony in diversity.